A holographic antenna approach for surface wave control in microstrip antenna applications - Sutinjo, Adrian; Okoniewski, M.; Johnston, R. (IEEE, 2010)
A holographic antenna inspired structure is used tocontrol the surface wave (SW) excited by a microstrip patch antenna.The hologram is designed to support a periodic leaky-wavewhich radiates at broadside and enhances the radiation of thepatch while suppressing the horizontal lobe. In this design, theholographic approach is adapted for patch antenna applicationswhere the SW wavelengths are comparable to the freespacewavelength. This is achieved by introducing dual phase-shiftingmetallic dipoles with periodic spacings. This paper discusses asimple and intuitive design method for the holographic surface,as well as its integration with the microstrip patch. The initialdesign concept was developed by assuming small perturbationto the SW, which was subsequently verified through full-wavesimulations and prototype measurements. The results verifiedthe improvements in the broadside gain and SW efficiency of themicrostrip patch at the cost of increased area.